Book Review. Issue 2 (1st June 2019) - Borrelli, Lisa Marie; Douglas, Cristina; Fontefrancesco, Michele
Abstract : Rules, Paper, Status: Migrants and Precarious Bureaucracy in Contemporary Italy Anna Tuckett. Stanford, CA: Stanford University Press, 2018, ISBN: 9781503606494, 192 pp., Pb. 25 Living before Dying: Imagining and Remembering Home Janette Davies. New York: Berghahn, 2018, ISBN: 978-1-78920-130-7, 158 pp., Pb. 27.95/£19.00. Unfinished: The Anthropology of Becoming João Biehl and Peter Locke (eds), Durham: Duke University Press, 2017, ISBN: 978-0-8223-6945-5, 400 pp., Pb. 29.95.